Regional game studies - Liboriussen, Bjarke; Martin, Paul (2016)
In the last few years there has been an increase in game scholarship conducted in and focussed on areas outside of Western Europe and North America. This scholarship has been recognized and supported by the establishment of regional research networks and regular regional conferences, and has been collected in edited books and journal special issues. Drawing on Edward Casey’s philosophical history of space and place we label this trend “regional game studies” and identify in it a number of general characteristics: regional game studies investigates games and gaming cultures at a range of scales and identifies connections across and between these scales; it highlights and addresses unequal global relations within gaming culture and within the academic study of games; and it enriches the field with new perspectives drawn from regional cultural contexts. The article provides a number of examples of regional game scholarship that demonstrate these characteristics and illustrate the potential of regional game studies to influence game scholarship and shape game studies as a field.